Chronic eosinophilic pneumonia presenting with ipsilateral pleural effusion: a case report. (December 2016) - Sriratanaviriyakul, Narin; La, Hanh; Albertson, Timothy
Abstract Background Chronic eosinophilic pneumonia is a rare idiopathic interstitial lung disease. The nearly pathognomonic radiographic finding is the peripheral distribution of alveolar opacities. Pleural effusions are rarely seen. We report a case of chronic eosinophilic pneumonia with transudative eosinophilic pleural effusion. Case presentation A 57-year-old Hispanic woman, a nonsmoker with a history of controlled asthma, presented to the hospital with unresolving pneumonia despite three rounds of antibiotics over a 2-month period. She was later diagnosed with chronic eosinophilic pneumonia based on the presence of peripheral blood eosinophilia, the peripheral distribution of alveolar infiltrates on chest radiograph, and a lung parenchymal biopsy with infiltrates of eosinophils. Upon presentation, our patient had a right-sided moderate-sized pleural effusion. The pleural fluid profile was consistent with a transudative effusion with eosinophil predominance. Our patient responded promptly to oral corticosteroid treatment in a few days. The pulmonary infiltrates and pleural effusion subsided on a 1-month follow-up chest radiograph after starting corticosteroid treatment. Conclusions We report the first case of chronic eosinophilic pneumonia presenting with pneumonia with ipsilateral transudative eosinophilic pleural effusion. Like other cases of chronic eosinophilic pneumonia, early recognition and diagnosis is essential and prompt treatment with corticosteroids is the mainstay of therapy. Pleural effusion resolved without the further need for therapeutic thoracentesis.